Kemampuan Kitin Dari Cangkang Kepiting Bakau (Scylla spp) dalam Menurunkan Kadar Kolesterol Jeroan Sapi - Subhan Hadi Kusuma (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
This study aims to determine the ability and optimum concentration of chitin shellmud crab (Scylla spp) in lowering cholesterol levels offal (brain) cows. The hypotheses  are  chitin  concentrations  varying  effect  on  cholesterol-lowering  beef offal.  The  method  used  is  an  experimental  method  by using pattern completely randomized  design  (CRD)  consisting  of  6  treatments  and  4  replications.  The treatment consists of P0 (-) (treatment of negative control), P0 (+) (treatment of positive control with chitosan 50 mg), P1 (chitin 30 mg), P2 (chitin 50 mg), P3 (chitin 70 mg), and P4 (chitin as much as 90 mg). Data were analyzed by analysis of variance (ANOVA) and  test Honestly Significant Difference (HSD). The results showed that the addition of chitin shell mud crab (Scylla spp) significantly (P 0.05) on cholesterol levels offal (brain) cows. Addition of chitin shell mud crab (Scylla spp) can lower cholesterol levels offal (brain) amounted to 82.04% cow. Decrease in cholesterol levels with the addition of chitin shell mud crab (Scylla spp) is more effective (82.05%) compared to commercial chitosan from shrimp shells (74.37%). The conclusions of this study are chitin concentrations varying effect on cholesterol- lowering beef offal. Addition of chitin shell mud crab (Scylla spp) as much as 70 mg/5 ml brain cholesterol-etanol  is the optimum concentration in lowering cholesterol levels in beef offal. Some suggestions are given in order to further research into better and perfect, namely the application of chitin into a capsule, in vivo testing, additional variables and modification of research and utilization of waste shells of crabs intensive in overcoming hipercholesterolemia.